Investigating the Performance of a 50MW CFB Boiler in a Coal-Fired Power Plant through Co-Firing with Gamal Biomass and RDF - Arifta Suryanugraha; Wibawa Hendra Saputera; Winny Wulandari (Journal of Social Research, 2025)
The co-firing program at coal-fired power plants (CFPP) is part of PT PLN (Persero)’s short-term strategy to support Indonesia’s Net Zero Emission (NZE) target by 2060. Biomass and Refuse-Derived Fuel (RDF) are among the promising co-firing fuels. Biomass is considered carbon-neutral, while RDF helps reduce environmental waste. This study evaluates the technical effects of co-firing Gamal and RDF at blending percentages of 5%, 15%, and 30%, focusing on boiler performance and plant efficiency. SteamPRO software by Thermoflow was utilized to simulate and analyze the power plant’s thermodynamic performance under each co-firing condition. The simulations show that fuel specification or fuel composition and calorific value significantly affect key performance parameters. Co-firing with Gamal increases the Net Plant Heat Rate (NPHR) from 3034 kcal/kWh (baseline) to 3065, 3136, and 3264 kcal/kWh for 5%, 15%, and 30% co-firing, respectively. Plant efficiency correspondingly declines from 28.35% to 28.05%, 27.42%, and 26.35%. Boiler efficiency also drops from 83.69% to 82.98%, 81.47%, and 78.92%. RDF, in comparison, results in smaller deviations, with NPHR reaching only 3062 kcal/kWh and plant efficiency decreasing slightly to 28.08% at 30% co-firing. The lower calorific value of Gamal (2481 kcal/kg) increases the total fuel flow and raises auxiliary power consumption in the draught system, especially in the PA, SA, and ID fans, whereas RDF causes only minimal deviations. Emission results show that Gamal, with 0.07% sulfur, reduces SO? emissions from 0.474 to 0.4326 kg/MWh at 30% co-firing, while RDF increases it to 0.4905 kg/MWh due to higher sulfur content (0.42%). Uncorrected CO? emissions rise with Gamal but decrease after applying the carbon-neutral factor, from 984 to 730 kg/MWh at 30%. These results emphasize the importance of co-firing fuel specification selection and blending percentage optimization to balance performance and environmental outcomes.